2019
DOI: 10.3390/biom9100579
|View full text |Cite
|
Sign up to set email alerts
|

Highly Sensitive and Rapid Characterization of the Development of Synchronized Blood Stage Malaria Parasites Via Magneto-Optical Hemozoin Quantification

Abstract: The rotating-crystal magneto-optical diagnostic (RMOD) technique was developed as a sensitive and rapid platform for malaria diagnosis. Herein, we report a detailed in vivo assessment of the synchronized Plasmodium vinckei lentum strain blood-stage infections by the RMOD method and comparing the results to the unsynchronized Plasmodium yoelii 17X-NL (non-lethal) infections. Furthermore, we assess the hemozoin production and clearance dynamics in chloroquine-treated compared to untreated self-resolving infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 38 publications
(61 reference statements)
1
12
0
Order By: Relevance
“…Measurements on parasite cultures indicated that RMOD had a limit of detection (LOD) of ∼10 parasites per µL of blood in samples spiked with P. falciparum 26 . These promising results were further supported by studies on P. berghei and P. yoelii-infected mice 23,24 . On an operational level, RMOD is promising as it can be conducted after a short training and provide test results within minutes.…”
mentioning
confidence: 65%
See 3 more Smart Citations
“…Measurements on parasite cultures indicated that RMOD had a limit of detection (LOD) of ∼10 parasites per µL of blood in samples spiked with P. falciparum 26 . These promising results were further supported by studies on P. berghei and P. yoelii-infected mice 23,24 . On an operational level, RMOD is promising as it can be conducted after a short training and provide test results within minutes.…”
mentioning
confidence: 65%
“…Rotating magneto-optical detection (RMOD) measurements. The concept of the rotating-crystal magneto-optical setup and the underlying physical principles of hemozoin detection are described in detail in our former studies [24][25][26] . The working principle is depicted in Fig.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For the 0.5% chloroquine assay, the following sampling point were applied after assay initiation: 8, 10, 12, 14, 16, 18, 20, 24, 32, 40 and 48 h. In the case of the 0.1% and 1% parasitemia piperaquine assays, sampling was carried out after 6, 8 and 10 h of incubation, and finally in case of the 1% parasitemia W2 strain treated with chloroquine, sampling took place 24 and 48 h after assay initiation. The scheme of the RMOD setup, as well as the underlying physical principles of the detection, are described in detail in our former studies [15][16][17] . Reproduction of this experimental scheme is possible by following the described details.…”
Section: Drug Solutionsmentioning
confidence: 99%